Simulation machining of titanium alloy (Ti-6Al-4V) based on the finite element modeling - Ali M.H.; Ansari M.N.M.; Khidhir B.A.; Mohamed B.; Oshkour A.A. (Brazilian Society of Mechanical Sciences and Engineering, 2023)
Titanium alloy is the most significant material used in the aviation industry because of their properties such as high strength and corrosion resistant. However, it is considered one of the most challenging areas for all industrialists due to their poor machinability. Therefore, machining process needs to be controlled by selecting the optimal cutting conditions to obtain the best machining responses at the same time which is very difficult and involves high cost. Hence, this review paper presents the investigation of an agreement between the simulation results and experimental findings to evaluate the finite element modeling (FEM) for prediction of the machining parameters of titanium alloy (Ti-6Al-4V). Computer-aided engineering tools, especially software which was used to perform the simulation. Four types of finite element software have been focused during the machining process of titanium alloy (Ti-6Al-4V) such as AdvantEdge, ABAQUS/EXPLICIT, DEFORM, and FORG software. The simulation results of FEM proved an agreement with the experimental data during the machining process of titanium alloy (Ti-6Al-4V). The FEM permits to reduce the cost of manufacturing in terms of prolonging the cutting tool life and saving machining time. © The Brazilian Society of Mechanical Sciences and Engineering 2013.